Rola patriarchatu rabinicznego w późnym antyku - Ciecieląg, Jerzy (Studia Europaea Gnesnensia, 2014)
The text focuses on the significant role of rabbinical patriarchate in Late Antiquity, in particular in the 4th and in the early 5th century. It discusses the main prerogatives of the patriarch, its legal and ideological foundations. Also, it addresses the relationships between the patriarchate and the Jewish population of Palestine and the Diaspora.